2016
DOI: 10.1039/c6ra03637f
|View full text |Cite
|
Sign up to set email alerts
|

A wash-durable polyelectrolyte complex that extinguishes flames on polyester–cotton fabric

Abstract: Polyester–cotton (PECO) blends were rendered flame retardant by depositing a stable polyelectrolyte complex as a wash-durable coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
(36 reference statements)
2
30
0
Order By: Relevance
“…The effectiveness of this polyelectrolyte coating is related to the extent of protonation of the amine groups. Previous work has shown that polyphosphates are ineffective flame retardants without the ammonium species nearby to cause formation of the phosphoric acid catalyst . This phenomenon is illustrated by comparing PEC 1,1 and PEC 1,10 , which have very similar weight gain.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The effectiveness of this polyelectrolyte coating is related to the extent of protonation of the amine groups. Previous work has shown that polyphosphates are ineffective flame retardants without the ammonium species nearby to cause formation of the phosphoric acid catalyst . This phenomenon is illustrated by comparing PEC 1,1 and PEC 1,10 , which have very similar weight gain.…”
Section: Resultsmentioning
confidence: 85%
“…This deposited complex is extremely insoluble at this point, owing to the strong ionic cross‐links formed by the interaction of the charged groups of PEI and PSP. These cross‐links render the coating resistant to dissolution by any further water exposure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note, that in spite of the many papers published recently in which applications of nanotechnology with the aim of improving non-halogen-containing, flame retardant efficiency [ 53 ] coupled with the interest in novel surface treatments mainly on cotton, such as sol–gel [ 39 , 54 , 55 , 56 , 57 ], layer-by-layer [ 39 , 54 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and atmospheric plasma [ 66 , 67 , 68 ], limited levels of flame retardancy and durability have often only been achieved. None of these treatments to the author’s knowledge has been either applied to or found to be acceptable in back-coating applications.…”
Section: Organobromine Flame Retardants—environmental Challengesmentioning
confidence: 99%
“…Layer-by-layer treatments applied to cotton and cotton/polyester blends, however, have recently demonstrated acceptable self-extinguishing properties during vertical fabric strip testing after a defined washing procedure. Notable among these are the recently published results of Grunlan et al [7,8]. All the above recent surface technologies are based on aqueous precursor treatments with the associated need for energy-intensive drying processes.…”
Section: Introductionmentioning
confidence: 99%